Integrated Dry NO sub x /SO sub 2 Emissions Control System baseline test report, November 11--December 15, 1991 - Shiomoto, G. H.; Smith, R. A. (Fossil Energy Research Corp., Laguna Hills, CA (United States), 1992)
The DOE sponsored Integrated Dry NOsub x/SOsub 2 Emissions Control System program, which is a Clean Coal Technology Ill demonstration, is being conducted by Public Service Company of Colorado. The test site is Arapahoe Generating Station Unit 4, which is a 100 MWe, down-fired utility boiler burning a low sulfur western coal. The project goal is to demonstrate 70 percent reductions in NOsub x and S0{sub 2} emissions through the integration of: (1) down-fired low-NOsub x burners with overfire air; (2) urea injection for additional NOsub x removal; and (3) dry sorbent injection and duct humidification for SOsub 2 removal. The effectiveness of the integrated system on a high sulfur coal will also be tested. This report documents the first baseline test results conducted during the program. The baseline tests were conducted with the original burners and auxiliary equipment and represent the unmodified boiler emissions. The burner design of Arapahoe Unit 4 results in relatively high NOsub x levels ranging from 740 to 850 ppM (corrected to 3% Osub 2, dry) over the load range. Excess air level was the primary factor influencing NOsub x emissions. During normal boiler operations, there was a wide range in NOsub x emissions, due to the variations of excess air, boiler load and other, secondary parameters. SOsub 2 emissions ranged from 350 to 600 ppM (corrected to 3% Osub 2, dry) and reflected variations in the coal sulfur content.